Trends in the implementation of the Paired Storytelling learning Model on Primary School Students’ Speaking Skills - Lelong, Rifhani Handayani; Yusuf, Faidah (Actual Insight, 2025)
This study systematically reviews 21 peer-reviewed articles published between August 2021 and December 2024 that examined the use of the Paired Storytelling learning model to improve primary school students’ speaking skills. Articles were selected from Google Scholar using defined inclusion criteria: (1) studies conducted in primary school contexts, (2) focus on speaking skills, (3) empirical research design, and (4) full-text availability. A content analysis was conducted across four dimensions: publication trends, research methodologies, participant characteristics, and data collection and analysis techniques. Results indicate a predominance of quantitative studies, particularly quasi-experimental designs, with minimal application of qualitative methods and Classroom Action Research (CAR). Most studies focused on upper-grade students (grades 4–6), while research on lower grades (1–3) was limited. Speaking tests and t-tests were the most frequently used tools. Key gaps include limited methodological variation, minimal exploration of early-grade learners, and underuse of advanced or mixed-method analyses. These findings underscore the need to diversify research approaches and target underrepresented student populations. Addressing these gaps can enhance our understanding of how Paired Storytelling fosters not only linguistic competence but also social interaction, learner confidence, and inclusive classroom engagement in primary education.